Acción vaso-periférica del extracto acuoso de las hojas de Clusia coclensis (Clusiaceae) - García-González, Mildred (1998)
Aqueous leaf extraet of Clusia coclensis was applied at a dose of 40 mglkg intravenously to isolated posterior extremities of six normotensive Sprague-Dawley rals and six Spontaneously Hipertensive rats anaesthelÍzed wíth sodium nembutal. The perfusion was done in the abdominal artery using as carrier Krebs bicarbonate ringer at 37°C and keeping constant perfusion pressures of 100 mmHg in normotensive rats and 150 mmHg in hipertensive rats. The venous return was measured in the inferior vena cava. The extract induced a significant reduction of the venous return begining 2 min after application, in both rat types. This may reflect a peripheral vasoconstriction that, in whole organism, would have an hipertensive effec!. Therefore, the mechanism of the alledgedly systemic hipotensive effeet of the aqueous extract of Clusia coclensis leafs resides probably at a central level, probably acting by a reduction of the con" tractibility of the myocardium.